2007
DOI: 10.1063/1.2431681
|View full text |Cite
|
Sign up to set email alerts
|

Weak localization and correlation effects in thin-film degenerate n-type silicon

Abstract: The magnetoconductance of thin-film n-type silicon has been studied in order to provide insight into the low-temperature behavior of recent silicon-based semiconductor-metal hybrid structures. There is considerable interest in such structures as potential candidates for creating nonmagnetic read-head sensors for ultrahigh-density recording. The magnetoconductance of thin-film silicon was therefore analyzed as a function of magnetic field orientation at temperatures ranging from T=4.2 to 300 K. At low temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…It is worthy noticing that the negative MR in our samples persists up to 9 T from 50 K to 30 K, which indicated that the weak localization effect persists up to the magnetic field of 9 T. This result agrees with some typical low-dimensional conduction systems [17,40,41]. However, in some other lowdimensional conduction systems [42,43], the MR is negative for moderate magnetic field, followed by a positive MR at higher magnetic field, which indicated that some other effect like regular orbital scattering may become more important at higher magnetic field. The dominating factors for the difference in low-dimensional conduction systems need to be further investigated.…”
Section: Resultssupporting
confidence: 88%
“…It is worthy noticing that the negative MR in our samples persists up to 9 T from 50 K to 30 K, which indicated that the weak localization effect persists up to the magnetic field of 9 T. This result agrees with some typical low-dimensional conduction systems [17,40,41]. However, in some other lowdimensional conduction systems [42,43], the MR is negative for moderate magnetic field, followed by a positive MR at higher magnetic field, which indicated that some other effect like regular orbital scattering may become more important at higher magnetic field. The dominating factors for the difference in low-dimensional conduction systems need to be further investigated.…”
Section: Resultssupporting
confidence: 88%
“…5 that show a factor of 3 diminished magnetoresistance in almost the same parallel field), and is not very probable because of thin potential well in Si-MOSFETs (∼ 3nm) compared to magnetic length l B [nm]= 25.7(B || [T]) −0.5 ; (ii) mobility may depend on Zeeman splitting in agreement with the predictions of the screening theory [27][28][29]. The latter mechanism should produce direction-independent positive magnetoresistance, exactly the behavior observed in heavilydoped multisubband thin Si quantum wells [64]. This however does not reconcile with our data.…”
Section: Discussionmentioning
confidence: 64%
“…No evidence of an inverted Hanle signal is observed, providing further evidence that the graphene layer has a smoothing effect that reduces interface roughness of the NiFe injector and thus minimizes accompanying fringe fields. Control samples using non-magnetic contacts show small positive magnetoresistance consistent with a Lorentzian type of magnetoresistance, ruling out weak localization, which might be more prevalent for these lower dimensional samples 58,59 . Both the amplitude (550 O) and linewidth are much larger than those of corresponding data obtained from NW samples which showed NLSV signals (Figs 3d and 4d).…”
Section: Resultsmentioning
confidence: 98%